Prognostic Value of Apolipoprotein E in Predicting One-year Mortality in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Li Y; Wu Q; Li Z; Xiao Y; Wei L (International Journal of COPD)
Yuqun Li,1,* Qilan Wu,1,* Zhenxing Li,1 Yang Xiao,2 Liping Wei1 1The Third Affiliated Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Department of Urology, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yang Xiao, Department of Urology and Guangdong Key Laboratory of Urology, First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China, Email dxxyang@126.com Liping Wei, The Third Affiliated Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China, Email weilp8@hotmail.comPurpose: Chronic obstructive pulmonary disease (COPD) is a serious disease with significantly higher mortality. Evidence suggests that there may be a co-relation between ApoE and the mortality risk in individuals who are diagnosed with COPD. This study sought to investigate the correlation between the levels of ApoE and all-cause mortality over one year in individuals who are diagnosed with acute exacerbations of chronic obstructive pulmonary disease (AECOPD).Methods: In this study, we checked serum ApoE concentrations of AECOPD patients on admission and collected the patients’ laboratory and clinical information. The co-relation between the concentration of ApoE and one year risk of all-cause mortality was analyzed by univariate, multivariate Cox regression and Subgroup analysis. Restricted Cubic Spline (RCS) were employed to illustrate the connection between ApoE levels and the hazard ratio (HR) for one-year total mortality rate.Results: Of the 449 participants who were enrolled, 358 patients were included in the study. The mean age was 76 (± 9.46) years old, of which 65.92% were male. The body-mass index was 22.18 (± 4.66). Of the participants, 24.86% were non-smokers, 54.75% were former smokers, and 20.39% were active smokers, with a smoking history of 28.68 (± 20.43) years. The restricted cubic spline curve revealed that patients exhibiting ApoE concentrations exceeding the mean value of 41.50 mg/L faced a notably higher risk of mortality in comparison to individuals with lower levels. In univariate analysis, the HR was 2.663 (95% CI 1.533– 4.627, P = 0.001), but in adjusted analyses, the HR was 2.103 (95% CI 1.19– 3.716, P = 0.01).Conclusion: Elevated levels of ApoE were independently risk factor for one-year mortality in patients with AECOPD. Subgroup analyses revealed that the association was stronger in younger patients (< 76 years) and male, as well as in those without comorbidities such as congestive heart failure or cerebrovascular disease. This suggests that ApoE may be a potential prognostic biomarker for AECOPD.Keywords: ApoE, AECOPD, mortality, prognostic biomarker